Analysis of The Potential of Indonesian Trading Commodities Through the Constant Market Share Analysis (CMSA) Method in the Indonesia-Republic of Korea Comprehensive Economic Partnership Agreement (IK-CEPA) Cooperation - Rini Febrianti; Erlambang Budi Darmanto; Rahmad Purnama; Taufik Hidayat (Alliance of Health Activists (AloHA), 2022)
Indonesia as a country that implements a free trade policy seeks to cooperate with various countries to obtain benefits both bilaterally and regionally. One form of trade cooperation currently carried out by Indonesia is the Indonesia-Korea Comprehensive Economic Partnership Agreement (IK-CEPA). The goal to be achieved is to find out the development of export, import, balance sheet, and free trade performance between Indonesia and South Korea during the last five years of 2017-2021. The method used is Constant Market Share Analysis (CMSA), which is a method that can identify Indonesian commodities/products that dominate, are competitive, and have high demand in South Korea. Meanwhile, Indonesian products that dominate in South Korea are raw material products / raw materials produced from natural resources such as coal, natural gas, copper ore, and palm oil. Keywords: Free Trade Agreements; Indonesia Korea Comprehensive Economic Partnership Agreement (IK-CEPA): Constant Market Share Analysis (CMSA)